Build N Burn: Using Fire as a Tool to Evoke, Educate and Entertain. Issue 2 (3rd July 2017) - Brophy, Kenneth; Goeckeritz, Corinna; Macgregor, Gavin
Abstract : The visceral nature of fire was exploited in the Neolithic and Bronze Age periods in Britain by the burning down of timber buildings and monuments, as well as the cremation of the dead. These big fires would have created memories, perhaps even 'flashbulb memories', and this powerful mnemonic aspect of fire was likely of significance to the social and religious lives of individuals, families and communities. This article introduces the Build N Burn concept, where fires are recreated and deployed alongside public talks, performances, experimental archaeology activities and demonstrations by craft specialists to create memorable and informative public events. Three public engagements to date, two on the island of Arran and one in Caithness, both Scotland, are described here. In each case, we constructed replica timber structures inspired by local prehistoric sites, and then burned these down in a free-to-attend public event at dusk, evoking the culmination of a prehistoric festival. Build N Burn has, at its core, the principle of delivering memorable experiences for the public inspired by prehistory, underpinned by research and experiment, using events which draw on cross-sectoral collaboration and working with local communities. This article offers a critical reflection on work to date, and discusses future potential for such activities, utilizing the mnemonic power and transformational potential of fire for public engagement and experimental archaeology.